Profil Burnout Profile of Final-Year Students at the Sekolah Tinggi Ilmu Dakwah (STID) Sirnarasa in the 2025/2026 Academic Year - Syarifah Hertiningsih; Yandi Cahya Yundani (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2026)
University students are in a phase of their education with much more complex academic demands than those at previous levels. They are required to think critically, make independent decisions, and possess effective communication skills as part of their academic readiness for college (Ansari et al., 2022; Vosniadou, 2020; Sari et al., 2025). Burnout is a significant issue among final-year students. According to Maslach & Jackson, there are three aspects of burnout: emotional exhaustion, depersonalization, and decreased academic performance. Therefore, the purpose of this study was to determine the burnout profile of final-year students at the Sirnarasa Islamic Da'wah College (STID) in the 2025/2026 academic year. This study used a descriptive quantitative method, with 48 items on a Likert scale, and was conducted with 27 final-year students. The results showed that final-year students did not experience significant burnout. Therefore, the burnout profile of final year students at the Sirnarasa Islamic College (STID) in the 2025/2026 academic year is in the low category.